Improving Financial Performance through Lean Six Sigma Implementation in the Banking Industry - Mahmudov, Rufat (2023)
This thesis aims to investigate the implementation of Lean Six Sigma (LSS) methodology in the banking industry to improve financial performance. The thesis uses a case study approach to investigate the loan processing process of a financial company using the DMAIC methodology. This study adds to the existing literature on LSS implementation by assessing the benefits and barriers associated with LSS implementation. The results were evaluated using a Likert scale. The project results were compared with the current literature, resulting in a systematic and objective assessment of LSS implementation in the banking sector. Each phase of the DMAIC methodology uses specific tools, including SIPOC, CTQ, Data Collection Plan, Control Charts, Process Cycle Efficiency (PCE), Ishikawa Chart, Poka Yoke and 5W1H. The analysis revealed significant opportunities to reduce waste and improve loan processing efficiency by identifying inefficient workflows as a key contributing factor. Implementing an automated document verification system using Poka Yoke reduced the lead time for the application verification step by 38%. These results help to practically understand and apply LSS tools in the loan processing business of the banking sector.